Using Content Maps to Measure Content Development in Physical Education: Validation and Application - (:unkn) unknown (HUMAN KINETICS PUBL INC, 2017)
Purpose: This study reports on our efforts toward extending the conceptual understanding of content development in physical education by validating content maps as a measurement tool, examining new categories of instructional tasks to describe content development and validating formulae that can be used to evaluate depth of content development. Method: The reliability, content, and concurrent validity of content maps and formulae were evaluated together with an application of the content maps and formulae. Descriptive statistics were used to report the data. Results: The reliability and validity of content maps was established. The new categories allowed for a finer analysis of content development. All formulae differentiated among different content expertise. Discussion/Conclusion: If depth of content knowledge is evidenced by tasks designed to refine, extend and apply student performance, then the content map, categories and formulae reported in this study provide tools that have utility for teachers, teacher educators and researchers.
Keywords: content knowledge; teacher education; pedagogical content knowledge; CONTENT KNOWLEDGE; TEACHERS